Analysis of IRI value for assessment of optimum maintenance strategy for low traffic volume roads in Nepal - Bala, Ramesh; Gautam, Ghana Shyam; Tamrakar, Gautam Bir Singh (Journal of Science and Engineering, 2017)
Road infrastructure is an important sector of economic activity for the development of a country. The road infrastructure is required to be maintained in proper condition to ensure its continuous utilization in proper manner. By proper maintenance of roads, continuous acceptability, a higher economy, safety and serviceability are gained. This research work was carried out through analysis of data collected from Department of Road (DoR) Nepal and surveyed through Google Earth. While analyzing data, data are categorized according to road type and pavement surface with spatial coverage. It mainly deals with the using of Road Economic Decision (RED) model, in which Highway Development and Management (HDM)-4 VOC model (Version 3.2) is used for computing coefficient of Vehicle Operating Cost (VOC) and RED Main Economic Decision model is used to compute value of International Roughness Index (IRI) for optimum maintenance strategy for strategic road network of Nepal with low traffic volume. The outcome of analysis will help the concern authority to make good decision on making priority and economical selection of maintenance strategy for the road having specified range of IRI value depending on the pavement type, surface type and volume of vehicle with spatial coverage.